Molecular Epidemiology and Antimicrobial Susceptibility of Clostridium difficile Isolates from a University Teaching Hospital in China - Cheng, Jing-Wei; Xiao, Meng; Kudinha, Timothy; Kong, Fanrong; Xu, Zhi-Peng; Sun, Lin-Ying; Zhang, Li; Fan, Xin; Xie, Xiu-Li; Xu, Ying-Chun (Frontiers in Microbiology, 2016)
While the developed world has seen a significant increase in the number of scientific articles on C. difficile infection (CDI), the developing world still lags behind on this subject due to limited laboratory capacity, low awareness and limited surveillance of this problem. As such, CDI is considered a neglected but potentially huge problem in developing countries. The major aim of this study was to systemically evaluate the utility of several molecular typing tools for CDI, including their relevance in epidemiological studies in developing countries such as China. A total of 116 non-repetitive toxigenic C. difficile isolates from Chinese patients, were studied. The isolates comprised 83 (71.6%) A+B+CDT- isolates, 27 (23.3%) A-B+CDT- isolates, and 6 (5.1%) A+B+CDT+ isolates. Typing methods evaluated included multilocus variable-number tandem-repeat analysis, PCR ribotyping, multilocus sequence typing, and sequencing of slpA and tcdC genes, which identified 113, 30, 22, 18, and 8 genotypes each and exhibited discriminatory powers of 0.999, 0.916, 0.907, 0.883 and 0.765, respectively. Compared to A+B+ strains, A-B+ strains exhibited higher prevalence of drug resistance to clindamycin, erythromycin, levofloxacin, rifampicin, rifaximin and tetracycline. Furthermore, drug resistance rates of strains with different PCR ribotypes differed, supporting the importance of molecular typing in management and control of CDI. Based on our earlier suggestion to improve the diagnostic laboratory capacity of CDI in developing countries, setting up efficient surveillance programs complemented by relevant molecular typing methods is warranted.